Pseudo-rheumatic manifestations of limping: Camptodactyly–arthropathy–coxa vara–pericarditis syndrome: Single case report and review of the literature - Maniscalco, Valerio; Pizzetti, Camilla; Marrani, Edoardo; Perrone, Anna; Maccora, Ilaria; Pagnini, Ilaria; Artuso, Rosangela; Simonini, Gabriele; Mastrolia, Maria Vincenza (Frontiers in Pediatrics, 2022)
Camptodactyly-arthropathy-coxa vara-pericarditis (CACP) syndrome is a rare genetic disease characterized by the tetrad camptodactyly, non-inflammatory arthropathy, coxa vara deformity, and pericardial effusion. The arthropathy typically affects large joints presenting with joint swelling in absence of other signs of inflammation. We described the case report of a girl affected by CACP syndrome caused by a new mutation in PRG4 gene (c.2831_2832insT; c.3892C>T), in which temporomandibular involvement was observed. The patient received treatment with intraarticular hyaluronic acid injections presenting rapid but transient improvement of pain and range of motion. A literature review of previously reported CACP patients has been performed. The 65.9% (87 out 132) of patients were Middle Eastern and consanguinity was reported in 62.8% (83) of cases. The median age of onset was 24 months (IQR 12-36 months) and median age of diagnosis 96 months (IQR 48-156 months). Arthropathy was always present, mainly involving hips (96.2%), knees (92.4%), wrists (89.4%), elbows (81.1%) and ankles (56.1%). Camptodactyly and pericardial effusion were described respectively in 97% (128) and 14.4% (19) of patients. The main radiological findings were coxa vara (96.2%), femoral changes (63.6%), intra osseus cysts (14.5%) and bone erosion (5,3%). The 34.1% (45) of patients had received a previous Juvenile idiopathic arthritis (JIA) diagnosis. CACP syndrome can be easily misdiagnosed with JIA. A prolonged lack of response to immunosuppressive therapy associated to typical clinical and radiological features should prompt to consider this rare syndrome.